The Effects of the Heavy and Chemical Industry Policy of the 1970's on the Capital Efficiency and Export Competitiveness of Korean Manufacturing Industries (Written in Korean) - 유, 정호 (KDI Journal of Economic Policy, 1991)
Korea's rapid economic growth of the past thirty years was led by extremely fast export growth under extensive government intervention. Until very recently, the political regimes were authoritarian and oppressed human rights and labor movements. Because of these characteristics, many inside and outside Korea are under the impression that the rapid economic growth was made possible by the government's relentless push for export growth through industrial targeting. Whether or not the government intervention was pivotal in Korean economic growth is an important issue because of its normative implications on the role of government and the degree of economic policy intervention in a market economy. A good example of industrial targeting policy in Korea is the "Heavy and Chemical Industry (HCI)" policy, which began in the early I970s and lasted for one decade. Under the HCI policy the government intervened in resource allocation through preferential tax, trade, and credit and interest rate policies for "key industries" which included iron and steel, non-ferrous metals, shipbuilding, general machinery, chemicals, and electronics. This paper investigates the effects of. the HCI policy on the efficiency of capital and the export competitiveness of manufacturing industries. For individual three-digit KSIC (Korea Standard Industrial Classification) industries and for two industry groups, one favored by HCI Policy and the other not, this paper: (I) computes capital intensities and discusses the impact of the HCI policy on the changes in the intensities over time, (2) estimates the capital efficiencies and examines them on the basis of optimal condition of resource allocation, and (3) compares the Korean and Taiwanese shares of total imports by the OECD countries as a way of weighing the effects of the policy on the industries' export competitiveness. Taiwan is a good reference, as it did not adopt the kind of industrial targeting policy that Korea did, while the Taiwanese and Korean economies share similar characteristics. In the I973-78 period, the capital intensity rose rapidly for the "HC Group/' the group of industries favored by the policy, while it first declined and later showed an anemic rise for the "Light Group," the remaining manufacturing industries. Capital efficiency was much lower in the HC Group than in the Light Group, at least until the late 1970s. This paper ascribes these results to excess investments in the favored industries and concludes that growth could have been faster in the absence of the HCI policy. The Korean Light Group's share in total imports by the OECD was larger than that of its Taiwanese counterpart but has become much smaller since I978. For the HC Group Korea's market share was smaller than Taiwan's and has declined even more since the mid-I970s. This weakening in the export competitiveness of Korea's industries relative to Taiwan's lasted until the mid-I980s. This paper concludes that the HCI policy had either no positive effect on the competitiveness of the Korean manufacturing industries or negative effects.